2020
DOI: 10.1021/acs.macromol.0c02384
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Film Morphology of Symmetric Six-Arm Star-Shaped Poly(methyl methacrylate)-block-Polystyrene Copolymers

Abstract: We investigated, via atomic force microscopy and fieldemission scanning electron microscopy, the thin-film morphology of six-arm star-shaped poly(methyl methacrylate)-b-polystyrene [(PMMA-b-PS) 6 ] with the volume fraction of PS block of ∼0.5. At smaller molecular weight (M) but higher than the critical molecular weight (M crit ) above which block copolymers start to microphase-separate, the thin-film morphology greatly depends on the surface tension at the air side when a substrate has preferential interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…According to our previous study, [31] (PMMA-b-PS) 6 thin film without confinement showed two different nanostructures (nanotubes and PL) depending on the film thickness and the affinity between the blocks and the substrate when the M of the (PMMAb-PS) 6 is ≈1.23 M crit . In this study, to investigate the effect of the affinity between the walls (and/or the bottom) and both blocks confined in the trench, we fixed M of (PMMA-b-PS) 6 as 1.23 M crit , where nanotubes are well-formed in thin film without confinement.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…According to our previous study, [31] (PMMA-b-PS) 6 thin film without confinement showed two different nanostructures (nanotubes and PL) depending on the film thickness and the affinity between the blocks and the substrate when the M of the (PMMAb-PS) 6 is ≈1.23 M crit . In this study, to investigate the effect of the affinity between the walls (and/or the bottom) and both blocks confined in the trench, we fixed M of (PMMA-b-PS) 6 as 1.23 M crit , where nanotubes are well-formed in thin film without confinement.…”
Section: Resultsmentioning
confidence: 85%
“…[20] Some research groups obtained diverse nanopatterns on a single substrate by controlling the microdomain orientation of the BCPs [21][22][23][24] or employing complex molecular architecture of BCPs. [25][26][27][28][29][30][31] Also, to obtain a long-range ordering of BCP microdomains on a substrate, the BCP self-assembly is combined with geometrical confinement, so-called graphoepitaxy, which is referred to as the directed self-assembly (DSA). [21,22,[32][33][34][35][36][37][38] Confinement of the BCPs can allow the control of the orientation of microdomains by adjusting the affinity between walls and blocks.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations